Frequency of Diabetic Retinopathy in already diagnosed cases of Diabetes Mellitus- A single center Experience - Aijaz Zeeshan Khan Chachar, Khushbakht Tanveer, Sana Arshad, Humaira Nazir, Mohamed Abdullahi Adam, Mohsin Asif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patients with diabetes mellitus ends up in many complications and retinopathy is one of the microvascular complications of this metabolic disease. Aim: To conclude the frequency of diabetic retinopathy in previously diagnosed patients of diabetes. Methods: Cross Sectional study was conducted in General Medicine Department, Fatima Memorial Hospital, Lahore. This study was conducted from 16th January 2021 to 16th July 2021. A total of 171 patients in both male and female with diabetes mellitus were involved in the study. All patients undertook fundoscopy to look for diabetic retinopathy in department of medicine. Non-probability consecutive sampling technique was used. Results: As per this study age series from 30 to 75 years with mean age of 51.099±6.19 years, mean duration of diabetes 9.304±3.60 years and mean weight was 87.713±7.63 Kg. Male patients were 64.9% and females were 35.1%. Diabetic retinopathy was seen in 36.8%. Conclusion: There is increase in prevalence of diabetic retinopathy with rise in period of diabetes mellitus. Keywords: Diabetes mellitus, Diabetic retinopathy, Duration of diabetes